Praktyka wdrażania CSR w polskich przedsiębiorstwach w opinii doradców - Rogowski, Robert (Annales. Etyka w Życiu Gospodarczym, 2016)
The paper presents the experiences of advisers in implementing the concept of CSRin Polish enterprises. The article presents the results of surveys covering such issuesas the implementation of CSR motives and actions taken by operators in the implementationof CSR policies. CSR advisors also identified that companies can useunethical practices. This is also a characteristic of CSR advisors.